Cooperative learning implementation among elementary trust school teacher program - Abdol Jani, Wan Nur Fuziana; Razali, Fazilah; Ismail, Normala (Institute of Advanced Engineering and Science, 2024)
Malaysia’s education system is continuously transforming to provide pupils with 21st-century skills. Cooperative learning is viewed as a student-centered approach that helps pupils develop 21st-century learner characteristics. This study aims to identify the relationship between teachers’ content knowledge, pedagogical knowledge, and technological knowledge with the implementation of cooperative learning. A total of 100 elementary Trust School Program teachers in Selangor were involved in this quantitative study, which comprises a correlational design. Respondents were randomly selected to answer the teachers’ cooperative learning questionnaire (TCLQ) and the content, pedagogical, and technological knowledge questionnaire. The findings obtained indicate that teachers’ content knowledge, pedagogical knowledge, and technological knowledge are at a high level. No significant difference was reported between teachers’ knowledge and implementation of cooperative learning based on years of teaching experience in Trust School Program. The result also revealed a positive and strong relationship between content knowledge and cooperative learning implementation (r=0.551, p=0.000), as well as a positive and strong relationship between pedagogical knowledge and cooperative learning implementation (r=0.603, p=0.000). However, a positive and moderate relationship was reported between teachers’ technological knowledge and cooperative learning implementation (r=0.384, p=0.000). This study can help raise awareness about the elements that educational policymakers and educators need to take into account during cooperative learning.